Pengaruh Servicecsape Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Di Cangkir Pertama Coffee Kota Purwakarta - mawardi, amna; Munawar, M Meki; Rahayu, Dewi (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of servicescape and service quality on customer satisfaction at the First Cup of Coffee, Purwakarta City. The research method used is descriptive quantitative. Sampling used a non-probability sampling method by distributing questionnaires to 97 respondents who were consumers at the First Cup of Coffee Purwakarta. Data analysis methods used are validity test, reliability test, normality test, linearity test, multiple regression analysis, correlation coefficient, coefficient of determination, hypothesis test, partial test (t test), and simultaneous test (F test). The data were processed using IBM SPSS version 24. The results showed that the two independent variables had an effect on the dependent variable, servicescape had a positive and significant effect on customer satisfaction at the First Cup of Coffee Purwakarta. Service quality has a positive and significant effect on customer satisfaction at the First Cup of Coffee Purwakarta. Simultaneously servicescape and service quality have a positive and significant effect on customer satisfaction at the First Cup of Coffee Purwakarta.